Transnational Television and Diaspora: Experiences of Pakistani Immigrants in Canada - Anjum Zia (JSSH, 2023)
Since 2002 Pakistan’s media landscape has witnessed transformational change, with more than 90 private and liberalized satellite television channels growing from just three state-run channels. These thriving transnational television channels broadcasting news, views, sports, religious, glamorous and entertainment programs in Urdu language; not only for the local audience but also caters the Pakistani Diaspora around the globe. Based on the notion that transnational media has the capacity to link diasporas to their homeland can have significant implications on immigrants; the present study looks at the experiences of Pakistani diaspora in Canada, with key investigation including involvement and importance of these channels in their lives.